Atrial tissue Doppler imaging for prediction of new-onset atrial fibrillation. Issue 10 (15th December 2008) - De Vos, C B; Weijs, B; Crijns, H J G M; Cheriex, E C; Palmans, A; Habets, J; Prins, M H; Pisters, R; Nieuwlaat, R; Tieleman, R G
Abstract : Background: The total atrial conduction time (TACT) is an independent predictor of atrial fibrillation (AF). A new transthoracic echocardiographic tool to determine TACT by tissue Doppler imaging (PA-TDI (the time from the initiation of the P wave on the ECG (lead II) to the A′ wave on the lateral left atrial tissue Doppler tracing)) has been developed recently. Objective: To test the hypothesis that measurement of PA-TDI enables prediction of new-onset AF. Methods: 249 Patients without a history of AF were studied. All patients underwent an echocardiogram and the PA-TDI interval was measured. Patient characteristics and rhythm at follow-up were recorded. Results: During a mean (SD) follow-up of 680 (290) days, 15 patients (6%) developed new-onset AF. These patients had a longer PA-TDI interval than patients who remained in sinus rhythm (172 (25) ms vs 150 (20) ms, p = 0.001). Furthermore, the patients developing AF were older, more often had a history of heart failure or chronic obstructive pulmonary disease, more often used α blockers, had enlarged left atria and more frequently mitral incompetence on the echocardiogram. After adjusting for potential confounders, Cox regression showed that PA-TDI was independently associated with new-onset AF (OR = 1.375; 95% CI 1.037 to 1.823; p = 0.027). The 2-year incidence of AF was 33% in patients with a PA-TDI interval >190 ms versus 0% in patients with a PA-TDI interval <130 ms (p = 0.002). Conclusions: A prolonged PA-TDI interval may predict the development of new-onset AF. This measure may be used to identify patients at risk in future strategies to prevent the development or complications of AF.